IMPLEMENTATION OF THE THINK PAIR SHARE COOPERATIVE LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING ACTIVITY IN SMK - Ita Darmayanti; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Mathematics is a basic science that has an important role in the development of science and technology. With the intensity of continuous mathematics learning, students should be able to master these subjects well. However, in reality, there are still many students dents who think that mathematic are complicated subjects with the application of formulas and calculation, students are less interested in mathematics, the level of student activity in mathematics learning is still lacking, the student is afraid to ask a question and express opinions, lack of student responsibility for the assignment given. This research aims to obtain a description of the application of cooperative learning of Think Pair Share (TPS) to improve student activity in class X Animation State Vocational High School(SMK Negeri) 3 Kasihan Bantul. This research is a classroom action research, which refers to the Kemmis and Mc. Taggart's design, those are (1) planning, (2) action, (3) observation, and (4) reflection. This research consists of two cycles, and each of the cycles was held in two meetings. The research subjects in this research are students of class X animation SMK Negeri 3 Kasihan Bantul, amounting to 31 people. This research object is learning mathematics using the cooperative learning model of think pair share—data collection techniques gained through observation, learning outcomes test, interview, and documentation. The data analysis technique in this research is qualitative descriptive. The result of this research, including that through applying cooperative learning of think pair share, can improve student activity of the system of three variable linear equations in class X animation SMK Negeri 3 Kasihan Bantul. The first cycle's student activity is 54,84% (enough category), and in the second cycle, it increases to 69,35% (good category).